mproving Posyandu Cadre's Understanding of Early Detection of Child Development in Watugede Village, Boyolali - Pristianto, Arif; Muhammad, Ardian Rifcky; Puspitaningrum, Dinda Ayudya (Prosiding University Research Colloquium, 2022)
The period of growth and development is a very important period, because growth and development affects and determines the ability of children in the future. At this time fine motor skills, gross motor skills, language, creativity, social awareness, emotional awareness, intelligence and psychological development are strongly influenced by the environment and the interaction between children and their parents. Early detection is a screening effort carried out to find deviations in growth and development disorders early and to know and recognize various risk factors for these growth and development disorders. Physiotherapy services offered are preventive and promotive. Preventive efforts aim to prevent delays in recognizing developmental disorders in children. Meanwhile, promotive efforts are aimed at optimizing children's growth and development. Preventive and promotive efforts are packaged in the form of counseling with presentation media. Evaluation of activities seen from the questionnaires given before and after counseling to the respondents. Based on the results of the counseling, there was an increased understanding of early detection by posyandu cadres on the growth and development of children in Watugede Village, Kemusu, Boyolali. By increasing this understanding, it is hoped that problems related to child development can be detected early. Of course, the right initial treatment will minimize the problems that arise related to the growth and development of children.